2021
DOI: 10.1140/epjp/s13360-021-02119-y
|View full text |Cite
|
Sign up to set email alerts
|

Joule–Thomson expansion of the torus-like black hole

Abstract: In this paper, we study the Joule-Thomson expansion of the torus-like black hole in extended phase space, where the cosmological constant is determined by the pressure. It is noteworthy that the torus-like black hole has a horizon of toroidal topology, rather than a horizon of spherical topology. We study both the inversion and isenthalpic curves of the torus-like black holes in the T − P plane and find that their intersection coincides with the inversion point that distinguishes the heat in the cooling proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…[ 46 ] These works indicated that, different from the van der Waals‐like fluid, the black hole in the AdS space has only a minimum inversion temperature, without a maximum one. The successive studies in various extended theories of gravity further confirmed these conclusions, [ 47–84 ] and the basic reason is the slight difference between the EoS of the black hole and the van der Waals‐like fluid.…”
Section: Introductionmentioning
confidence: 75%
“…[ 46 ] These works indicated that, different from the van der Waals‐like fluid, the black hole in the AdS space has only a minimum inversion temperature, without a maximum one. The successive studies in various extended theories of gravity further confirmed these conclusions, [ 47–84 ] and the basic reason is the slight difference between the EoS of the black hole and the van der Waals‐like fluid.…”
Section: Introductionmentioning
confidence: 75%
“…Furthermore, Lemos and Zanchin [52] found another solution of a torus-like BH by figuring out the Einstein-Maxwell field equation with AdS space-time, and such solution is said to be black string. Liang et al [53] investigate the Joule-Thomson expansion of a torus-like BH in an extended phase space. They have come to the conclusion that in contrast to spherical BHs, the torus-like one possesses a horizon that has a toroidal topology.…”
Section: Introductionmentioning
confidence: 99%